2019
DOI: 10.3390/coatings10010004
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Optimization of Two-Component Waterborne Polyurethane Locomotive Coating

Abstract: This paper reports the effects of different formulas on the performance of waterborne polyurethane (WPU), including two-component WPU and curing agent, wetting dispersant, defoaming agent, and wetting agent. The optimization of rheological additives selection, through the optimization of coating physical properties and chemical properties, can make the film show uniform color and appearance without pinholes, bubbles, or wrinkles, and have a long probation period. Through the analysis of performance after a 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As has already been mentioned, PURs are, in most cases, two-component systems whereby the individual components are supplied separately in liquid or semi-liquid states and the final curing process occurs only after they have been properly mixed together [ 12 , 13 , 14 ]. Common 2K systems are simply PURs or epoxies and silicones.…”
Section: Introductionmentioning
confidence: 99%
“…As has already been mentioned, PURs are, in most cases, two-component systems whereby the individual components are supplied separately in liquid or semi-liquid states and the final curing process occurs only after they have been properly mixed together [ 12 , 13 , 14 ]. Common 2K systems are simply PURs or epoxies and silicones.…”
Section: Introductionmentioning
confidence: 99%
“…They found that coatings based on resins with more hydroxyl groups typically have a stronger wet adhesion and salt spray resistance. According to Liu et al [14], the performance of waterborne polyurethane was affected by various formulations of the two components as well as its curing agent, wetting dispersant, defoamer, and wetting agent. The prepared two-component waterborne polyurethane topcoat had a high gloss and high weather resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the polyurethane coatings, bubble-free film thickness (BFFT) is used to describe the index of two-component waterborne polyurethane coatings [ 14 ]. At present, BFFT of waterborne polyurethane coatings is about 80 μm, which is lower than that of solvent-based coatings (which is about 100 μm) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%